2017
DOI: 10.1109/tnsre.2017.2712707
|View full text |Cite
|
Sign up to set email alerts
|

Is Implicit Motor Imagery a Reliable Strategy for a Brain–Computer Interface?

Abstract: Explicit motor imagery (eMI) is a widely used brain-computer interface (BCI) paradigm, but not everybody can accomplish this task. Here, we propose a BCI based on implicit motor imagery (iMI). We compared classification accuracy between eMI and iMI of hands. Fifteen able-bodied people were asked to judge the laterality of hand images presented on a computer screen in a lateral or medial orientation. This judgment task is known to require mental rotation of a person's own hands, which in turn is thought to invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
8
2
Order By: Relevance
“…The bimanual MI task had parietal ERD more spread over the non-dominant hemisphere but the intensity was not significantly stronger than during unimanual MI tasks. Contrary to the results of our previous study on another group of healthy participants [43] we found no significant difference between ERD during MI of the left and the right hand. That might explain somewhat lower classification accuracy of L-R classifier in this study vs 83±3% in [43].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The bimanual MI task had parietal ERD more spread over the non-dominant hemisphere but the intensity was not significantly stronger than during unimanual MI tasks. Contrary to the results of our previous study on another group of healthy participants [43] we found no significant difference between ERD during MI of the left and the right hand. That might explain somewhat lower classification accuracy of L-R classifier in this study vs 83±3% in [43].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the results of our previous study on another group of healthy participants [43] we found no significant difference between ERD during MI of the left and the right hand. That might explain somewhat lower classification accuracy of L-R classifier in this study vs 83±3% in [43]. On average 20% people cannot use MI BCI [44] which might reflect on differences in classification accuracy between healthy volunteers.…”
Section: Discussioncontrasting
confidence: 99%
“…Mental rotation of a body part involves motor imagery of that body part, and both processes activate sensorimotor areas [84]. Because subjects are not necessarily aware of movement imagination during mental rotation, Osuagwu et al referred to it as implicit motor imagery [85]. Implicit motor imagery is an automatic process that does not depend on the capacity of consciously imagined movements.…”
Section: Solving the Mi‐bci Inefficiency Problemmentioning
confidence: 99%
“…MI has been used widely in BCI. By imagining or performing a muscle movement action, the power of mu (8)(9)(10)(11)(12)(13) and beta (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) rhythms in the sensorimotor cortex will decrease or increase. Researchers hypothesized that an appropriate pattern of this phenomenon can be used as a suitable feature/signature in the classification.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], after some pre-processing method like band pass filtering (BPF) and independent component analysis (ICA) to remove artifacts, CSP was employed to design spatial filters for each class of signal and LDA was used as a classifier. Osuagwu et al [16] achieved a maximum accuracy of 81 ± 8% for explicit MI and 83 ± 3% for implicit MI method in discrimination between left and right hand. Some other studies suggested combining some methods to achieve better results.…”
Section: Introductionmentioning
confidence: 99%